APPRAISAL SYSTEM ANALYSIS IN CATATAN PINGGIR GOENAWAN MOHAMMAD IN TEMPO MAGAZINE - Alindah, Lutfiyah (Universitas Negeri Surabaya, 2024)
This study examines the aspects of the appraisal system in Goenawan Mohammad's Catatan Pinggir in Tempo magazine and explores the author's ideology conveyed to the readers. The data were taken from Goenawan Mohammad's Catatan Pinggir, published in Tempo magazine in December 2011. The data collection was carried out by observing free-of-talk. These data were analyzed using an appraisal analysis framework based on Halliday's theory of interpersonal meaning in Functional Systemic. The result shows that in Catatan Pinggir, written by Goenawan Mohammad through the appraisal tool, the author's attitude was identified to be conveyed to the readers. The attitude that the author wants to convey is an attitude of mutual respect and openness to differences. Based on this attitude, the author's ideology is that the author wants an attitude of mutual love and respect without seeing any differences.